Contrivance of Augmented Reality with Interior Designing - Hebbar, Prajna; Deepa, B. G.; Bhuvan, N.; Ranganth, N. (Artificial Intelligence and Applications, 2025)
In the modern day, design is an integral part of our life, so there is a need of interior design. Interior design is gaining its popularity day by day. But the major problem faced by people while looking for designing any interior is that hiring interior designers and booking design session with them are time consuming and are deemed quite expensive. Hence to eliminate these two pain points, this project proposes the design about a software platform where users can design their own space with the assistance of augmented reality which is a huge contribution to the digital world having a variety of applications. This project includes mainly the process of designing an application that is identifying problem, meeting business requirements, identifying the main users and the tasks they do in this app, building a scenario, creating a task flow for a scenario, and finally presenting main screens of the main task flow. Received: 10 July 2022 | Revised: 20 September 2022 | Accepted: 28 September 2022 Conflicts of InterestThe authors declare that they have no conflicts of interest to this work. Data Availability StatementData sharing is not applicable to this article as no new data were created or analyzed in this study. Author Contribution StatementPrajna Hebbar: Conceptualization, Methodology, Software, Validation, Formal analysis, Investigation, Resources, Data curation, Writing - original draft, Writing - review & editing, Visualization. B. G. Deepa: Conceptualization, Methodology, Software, Validation, Formal analysis, Investigation, Resources, Data curation, Writing - original draft, Writing - review & editing, Visualization, Supervision, Project administration. N. Bhuvan: Software, Validation, Investigation, Resources, Data curation, Visualization. N. Ranganth: Validation, Resources, Data curation, Visualization.
Keywords: design; user interface; interior; augmented reality (AR)